Keeping Talents in the Transport and Logistics Enterprises: Case Study from the Czech Republic - Lizbetinova, Lenka; Nedeliakova, Eva; Soušek, Radovan; Gregus, Michal (Budapest tech, 2020)
The aim of the article is to identify the motivation preferences of Czech managers on critical management positions of transport and logistics enterprises and to determine the method for the effective setting of the motivation factors in the interest of keeping them in an enterprise. The article is based on research outcomes from transport and logistics enterprises where the focus is on managers identified as talents by the enterprises. Research was conducted in 2018 in the Czech Republic using a questionnaire. In research, 154 managers were interviewed. Data were processed using basic descriptive statistics. The proposed effective setting of motivational elements is based on the use of a method for determining an appropriate variant - AHP multicriteria decision making method. The results of the article can serve to help entrepreneurs not only in the field of transport and logistics services. Other enterprises also have the potential to gain a strong system not only to retain their talents in society, but also to create satisfaction and commitment to the enterprises. The presented way of setting motivation factors is universally applicable to any sector and regional location.
Vedení talentů v dopravních a logistických podnicích: Případová studie z České republiky
Keywords: talents; managers; transport and logistics enterprises; AHP decision method; talent; manager; doprava; logistika; pracovní podmínky